Quality, productivity, and learning in framework-based development an exploratory case study. - Morisio, M.
This paper presents an empirical study in an industrial context on the production of software using a framework. Frameworks are semicomplete applications, usually implemented as a hierarchy of classes. The framework is developed first, then several applications are derived from it. Frameworks are a reuse technique that supports the engineering of product lines. In the study, we compare quality (in the sense of rework effort) and productivity in traditional and framework-based software production. We observe that the latter is characterized by better productivity and quality, as well as a massive increase in productivity over time, that we attribute to the effect of learning the framework. Although we cannot extrapolate the results outside the local environment, enough evidence has been accumulated to stimulate future research work.
Keywords: Framework-based development; Learning; Product line engineering; Productivity; Quality; Reuse technique; Semicomplete applications; Software production